Soft robotics : trends, applications and challenges : proceedings of the Soft Robotics Week, April 25-30, 2016, Livorno, Italy - Laschi, Cecilia; Rossiter, Jonathan; Iida, Fumiya; Cianchetti, Matteo; Margeri, Laura (Springer, 2017)
"This book offers a comprehensive, timely snapshot of current research, technologies and applications of soft robotics. The different chapters, written by international experts across multiple fields of soft robotics, cover innovative systems and technologies for soft robot legged locomotion, soft robot manipulation, underwater soft robotics, biomimetic soft robotic platforms, plant-inspired soft robots, flying soft robots, soft robotics in surgery, as well as methods for their modeling and control. Based on the results of the second edition of the Soft Robotics Week, held on April 25-30, 2016, in Livorno, Italy, the book reports on the major research lines and novel technologies presented and discussed during the event."--Provided by publisher.
Keywords: Robotics -- Congresses.; Soft computing -- Congresses.; elektronické knihy; electronic books